Projected changes to drought characteristics in Tehran under CMIP6 SSP-RCP climate change scenarios - Mohammad Reza Khazaei (Heliyon)
Drought represents one of the most devastating natural hazards, significantly impacting economies, societies, and the environment. Climate change is expected to alter future drought characteristics and may increase the severity of droughts. To mitigate these effects, it is essential to identify the characteristics of future droughts influenced by climate change using appropriate methods. This study aims to assess the climate change impacts on the frequency, duration, and magnitude of droughts in Tehran, the capital of Iran, which has a high concentration of the country's population and industrial activities and is currently facing water stress. Using the Modified Long Ashton Research Station Weather Generator (M-LARS-WG), capable of reproducing inter-annual variability, future projections from four GCMs under four SSP-RCP scenarios from the latest CMIP6 were downscaled. The impacts of climate change on droughts were then assessed using the SPEI and SPI drought indices. The findings suggest that M-LARS-WG was capable of accurately reproducing historical drought characteristics and performed significantly better than LARS-WG. Based on the SPEI, the duration, magnitude, and frequency of future droughts are expected to increase significantly across nearly all GCM projections. Therefore, developing proactive drought risk frameworks and mitigation strategies is essential for reducing damages from future droughts.